2003
DOI: 10.1188/03.onf.834-840
|View full text |Cite
|
Sign up to set email alerts
|

Family Beliefs About Diet and Traditional Chinese Medicine for Hong Kong Women With Breast Cancer

Abstract: Many Chinese families have different beliefs about food and diet and the role that food plays in managing the cancer experience. Often, Chinese people will not seek clarification if they do not understand information. If information does not fit with their predominant belief systems, families may not implement it, nor will they discuss a situation if they think the conversation will result in a relationship of conflict with healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Findings that cancer patients in Hong Kong favored Chinese herbal medication are consistent with previous studies [9,22]. The present study discovered that nearly half (49.93%) of the participants recruited from Western medicine clinics used Chinese medicine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings that cancer patients in Hong Kong favored Chinese herbal medication are consistent with previous studies [9,22]. The present study discovered that nearly half (49.93%) of the participants recruited from Western medicine clinics used Chinese medicine.…”
Section: Discussionsupporting
confidence: 92%
“…The present study indicates that the use of Chinese medicine in cancer treatment in Hong Kong (57.1%) is much more than that in Japan (7.1%) [7], but lower than that in the mainland China (100%) [6]. As overseas Chinese often think of Chinese medicine as their first choice of CAM [22,23], this difference in the use of Chinese medicine may be due to socio-cultural difference among ethnics groups [22] rather than regional differences in medical systems.…”
Section: Discussionmentioning
confidence: 87%
“…In TCM, “chi” represents a concept of energy; yin-yang imbalance in chi may result in physical vulnerability[52,53]. The uptake of alternative medicine is common among cancer patients, especially when their physical problems are not resolved with biomedical treatments[54-59].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese American women have reported that cancer is caused by diet (Simpson, 2003), immoral behavior (Wong-Kim et al, 2003), fate (Wong-Kim et al, 2003), and accumulation of anger (Simpson, 2003). Similarly Korean Americans believe that diseases, including cancer, are caused from excess negative forces such as chronic anger, misconduct, negative attitudes, or stress (Kim, Menon, Wang, & Szalacha, 2010).…”
Section: Culture Health Beliefs and Health Behaviorsmentioning
confidence: 99%